YOGA AS A COMPLEMENTARY THERAPEUTIC INTERVENTION FOR REDUCING ANXIETY IN BREAST CANCER PATIENTS: A LITERATURE REVIEW - Maryati, Ida; Putri, Della Yasinta; Hamidah, Nabila Aulia; Tisna, Muhamad Den; Bafadhal, Syane Koesavitri; Fariza, Yuanita Maudy; Rafi, Rifan Muhammad; Rausanfikra, Syiffa Salsabila (Journal of Maternity Care and Reproductive Health, 2026)
Anxiety is a common psychological problem experienced by breast cancer patients and can negatively impact quality of life and treatment adherence. Several studies have evaluated yoga as a complementary therapy to reduce anxiety in breast cancer patients, but these research results are still scattered and have not been systematically summarized. Therefore, this article aims to conduct a systematic review to evaluate the effectiveness of yoga as complementary therapy in reducing anxiety levels in breast cancer patients. The method used is a systematic review with the PICO approach (Population: breast cancer patients; Intervention: yoga; Comparison: standard care or without yoga; Outcome: anxiety level). The literature search was conducted through four electronic databases: ScienceDirect, EBSCO Host, PubMed, and Springer. The article selection process followed the PRISMA guidelines. Of the total articles obtained during the initial search stage, 8 article met the inclusion criteria: articles in English, published between 2020-2025, using a Randomized Controlled Trials (RCTs) or Quasi-Experimental design, and involving adult patients with breast cancer. The review results indicate that yoga is effective in reducing anxiety levels, increasing relaxation, and improving the psychological well-being of breast cancer patients. Further research is recommended using experimental designs with large sample sizes to strengthen the evidence for yoga’s effectiveness in breast cancer patients.